Uniquely human : a different way of seeing autism - Prizant, Barry M. (Simon & Schuster, 2015)
Autism is usually portrayed as a checklist of deficits, including difficulties interacting socially, problems in communicating, sensory challenges, and repetitive behavior patterns. This perspective leads to therapies focused on ridding individuals of "autistic" symptoms. Now Dr. Barry M. Prizant, an internationally renowned autism expert, offers a new and compelling paradigm: the most successful approaches to autism don't aim at fixing a person by eliminating symptoms, but rather seeking to understand the individual's experience and what underlies the behavior.